The Soviet challenge: the industrial revolution in Russia - Encyclopaedia Britannica Films (Chicago, III. : Encyclopaedia Britannica Films, 1962)
Sumario: Documental sobre la modernizacion de la antigua Rusia y la Revolucion Industrial.
En espanol.
An essay on war. -- Chicago, Ill. : Encyclopaedia Britannica Educational Corporation, c1978.
Keywords: UNION SOVIETICA -- CONDICIONES ECONOMICAS; UNION SOVIETICA -- INDUSTRIAS